If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 5 + -6x = 12 Reorder the terms: 5 + 7x + -6x = 12 Combine like terms: 7x + -6x = 1x 5 + 1x = 12 Solving 5 + 1x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 1x = 12 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 12 + -5 1x = 12 + -5 Combine like terms: 12 + -5 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| 5/7=k/42 | | -6(w-8)-(9+8w)=-15w | | 5y-3(y-1)= | | -3y-10=5x+14 | | 6/3=y/6 | | 1100=1220-20p | | 9x-17=100 | | 48/k=8/5 | | -4+10=16x-2-15x | | 6(x-3)=9+5x | | 4pq+q= | | 2/7a=7 | | 2-y=19 | | 8-2(4-3m)= | | 24+x-6=50+6 | | 7(y+2)+y=4(y+2)+7 | | 8y=3y+18 | | d^2+5/2d+3/2=0 | | 6x+6-2x=1+3x-1 | | 6y=4x | | 28ab-7a-8b+2= | | -250.00+75.00w=500.00 | | 9-5x=3x-46 | | x^1/3=0 | | 5/6x=-10 | | (4x-2)=90 | | x^4-3-x^3+125=0 | | 5z=12-22 | | 4x^2-1-x(2x+1)=0 | | 1+(x-3)/3=(2x+1)/6-2 | | 0=3y^2-19y+22 | | 2x+8=-31+7x |